Activating students’ prior knowledge of basic science concepts on animal and human system organ - Mochammad Ahied; Aida Fikriyah; Irsad Rosidi; Laila Khamsatul Muharrami (Universitas Negeri Jakarta, 2020)
This study aimed to analyze students' prior knowledge of basic science subjects, especially in organ systems concepts in animals and humans. This research was conducted on the lecture of Basic Science toward 46 students in Science Education class. Data were collected using a diagnostic test consisting of 12 essay questions in the first meeting before the learning process was implemented. Furthermore, findings obtained in this study were analyzed using quantitative descriptive method. Findings of the study indicated that students’prior knowledge reached a low level, with 4.8 on the average score. From out of 46 students in this study, six students reached high prior knowledge score. In contrast, 40 students reached below a high level. It can be concluded that students do not have great prior knowledge. It should be stimulated continually in every initial learning process to comprehend the new concepts during learning activities easily.